Особливості периферичного кровотоку в жінок-курців - Апончук, Людмила; Aponchuk, Liudmyla (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Дослідження присвячено вивченню стану показників периферичної гемодинаміки в жінок-курців. Проана- лізовано стан показників периферичної гемодинаміки в жінок, які палять, та контрольної групи досліджуваних. Показники периферичного кровотоку статистично значимо вищі в жінок, які курять (дослідна група). Це вказує на порушення периферичного кровотоку, що призводить до зменшення еластичності й тонусу судинного русла, а також порушення симетричного кровонаповнення кінцівок. The aim of our study was to explore the peculiarities of peripheral hemodynamics of upper and lower limbs in female smokers. During our studies of peripheral hemodynamics of upper and lower limbs the following peculiarities have been found. The research showed a valid difference between the values of the parameters in the experimental group and the control group. In the experimental group one could witness poor blood circulation, which reduces the elasticity and tone of the vascular bed and violates symmetrical blood supply in the limbs. The coefficient of asymmetry of right and left forearms in the experimental group was higher than in the control group. This indicates uneven blood flow of the upper limbs and lack of nourishment of tissues in certain areas. It also indicates long lasting violations of blood circulation resulting in disrupted nourishment of tissues and damaged vascular walls which in its turn lead to their irreversible extension. Statistically significant differences between the studied groups were also found in symmetrical distribution of peripheral blood flow in the lower extremities. In other words, long lasting smoking affects the immune, nervous and endocrine systems. The immune system reduces emissions of the special enzymes, which have protective function, to the blood; the cellular immunity system weakens.
Peculiarities of peripheral blood flow of female smokers.
Keywords: периферична гемодинаміка; кровообіг; тютюнокуріння; жінки-курці; peripheral hemodynamics; blood circulation; smoking; female smokers